Upaya Hukum Hak Penyandang Disabilitas Selama Masa Pandemi Covid 19 di Indonesia - Muflih Ramdhani; asmuni (Jurnal Ilmu Sosial dan Humaniora, 2022)
The COVID-19 pandemic threatens all humans in the world. Many people died due to the plague of the world that has not disappeared yet from human civilization. Ministry of Social Affairs in 2021 through the Management Information System for Persons with Disabilities as of January 13, 2021, there were 209,604 persons with disabilities in Indonesia. This figure is a reference that there are quite a lot of people with disabilities that need to be considered with a large number of people with disabilities. Persons with disabilities are a group that is vulnerable to today's conditions, the spread of the COVID-19 pandemic in Indonesia. This research aims to determine the government's legal responsibility for persons with disabilities during the COVID-19 pandemic in Indonesia through regulations and legal remedies for handling them. This research uses the juridical-normative method and the conceptual approach and the statute Approach. The results of this study reveal that Persons with Disabilities have a right to health that cannot be reduced and requires the presence of the government to protect fundamental rights, that is the right to health which is included in human rights that have been stated in the laws and regulations in Indonesia. The fulfillment of rights for persons with disabilities during the COVID-19 pandemic has not been fully regulated and implemented by the government. It has been proven in several cases that there is discrimination against persons with disabilities in obtaining easy access and protection during the COVID-19 pandemic.